Restructuring Nepalese Societies through Residential Relocation and Its Social Effects - Silwal, Keshab Raj (Journal of Nepalese Studies, 2025)
This paper focuses on the voluntary relocation of residents of Nepalese society and its effects on social relationships, which unfolds the restructuring and transforming of the old residential structure of Nepalese society. Some scholars attribute the individual factors to the residential relocation and exemplify the life-cycle changes of household heads or household composition, such as the age, employment, or marital status of the household head and the number of children (Rossi, 1955).  They believe that the increase of marriage rate and fertility rate are determinative conditions for the residential relocation and rapid expansion of suburban areas. Besides these arguments, many scholars have embraced various facets of social change with residential relocation and find that most residents move to significantly higher-income and less racially segregated suburban neighborhoods with access to better infrastructure, services, and amenities (Deluca et al., 2005; Diewald and Mayer, 2009). Suburban growth is propelled by transportation and technology development, such as mass-produced automobiles and highways. It is an interesting social phenomenon in Nepal that the residents from hilly and remote areas are relocating downward and close to market areas. Drawing on the fieldwork in Lele Valley, Lalitpur District—an emerging suburban area—this paper examines how people prefer to relocate their residences near to market and transport facilities, creating a new social relationship. It is found that they relocate their residents because of income sent from their family members who are in foreign employment or they sell their land. They introduce a new type of nexus and relationship with new neighbors who are not among their kinship and start bonding on every occasion.